Iron and manganese removal in direct anoxic nanofiltration for indirect potable reuse - Jin, Yongxun; Choi, Yeseul; Song, Kyung Guen; Kim, Soyoun; Park, Chanhyuk (TECHNO-PRESS, 2019)
Managed aquifer recharge (MAR) systems are gaining interest as an alternative to conventional water resources. However, when the water recovered in MAR systems, dissolved iron and manganese species may easily oxidize and they cause well screen clogging or require abandonment of extraction wells. In this study, both oxic and anoxic conditions were analyzed to verify the feasibility of the membrane filtration performance under various solution chemistries. The fouling mechanisms of the metal ions under anoxic conditions were also investigated by employing synthetic wastewater. The fouled membranes were then further analyzed to verify the major causes of inorganic fouling through SEM and XPS. The newly suggested anoxic process refining existing membrane process is expected to provide more precious information about nanofiltration (NF) membrane fouling, especially for demonstrating the potential advantages to chemical-free drinking water production for indirect potable reuse.
Keywords: AQUIFER STORAGE; FOULING INDEX; MEMBRANE; WATER; GROUNDWATER; RECOVERY; SYSTEMS